Efficiency Decomposition in Two-Stage Network in Data Envelopment Analysis with Undesirable Intermediate Measures and Fuzzy Input and Output - Fatima Saeedi Aval Noughabi; Najmeh Malekmohammadi; Farhad Hosseinzadeh Lotfi; Shabnam Razavyan (Fuzzy Information and Engineering, 2022)
This paper presents a model for the efficiency evaluation of decision-making units comprising a network structure with undesirable intermediate measures. This model is then generalised to evaluate the efficiency of network decision-making units with triangular fuzzy data and undesirable intermediate measures. In this study, data envelopment analysis (DEA) models with fuzzy network structures and undesirable intermediate measures are considered and solved as linear triangular fuzzy planning problems. With numerical results, the application of the proposed model in the chipboard industry of wood lumber has been shown.